데이터베이스(DB)를 이용한 상한론(傷寒論) 조방(組方)의 분석(分析) - 계지탕(桂枝湯), 마황탕(麻黃湯), 대청룡탕(大靑龍湯)을 중심으로 - 김성원; Kim Sung-won; 김기욱; Kim Ki-wook; 이병욱; Lee Byung-wook (大韓韓醫學原典學會誌, 2019)
Objectives : This study analyzes herbs combinations and primary virtues that constitute the prescriptions of Gyeji-tang, Mahwang-tang, and Daecheongryong-tang to effectively analyze medication preparations described in "Shanghanlun" using database, and test the results of the data structure and effectiveness of queries. Methods : This study enters "Sanghanjapbyeongronyeonggudaeseong" as the original text into the database, and even uses one provision as independent knowledge by dividing provisions in accordance with the content. Results : Five tables and 12 queries were created and used for data input and analysis. Using the types of Herbs included in the prescriptions, this study manages to search for the same or supplemented prescriptions, and the primary virtues of the prescriptions were collected and compared. Conclusions : Subject to the combination of herbs and pathology for the prescriptions described in "Shanghanlun" utilizing the database, this study found relevant texts and combinations of herbs and pathologies, and using this, the time required for theoretical research between prescriptions could be shortened.